PEMBUATAN BUKU GRAPHIC NOVEL HIKAYAT CANDI PRAMBANAN SEBAGAI UPAYA PENGENALAN SEJARAH BUDAYA KEPADA ANAK-ANAK - Dwinanto, Denny; Dewanto, Thomas Hanandry; Fahminnansih, Fenty (Jurnal Art Nouveau, 2015)
Abstract: The purpose of the creation of the Graphic Novel biography of Prambanan Temple is to introduce and preserve the folklore of particular legend Roro Jonggrang. Research conducted using qualitative research methods, namely by doing interviews, observation, documentation, library and study to get the data used as the supporter of the creation of the concept design of branding. The data were analyzed by using multiple stages, namely the reduction of the data, the presentation of data, and conclusions. From the analysis of the data found few keyword refers to a strategy of making books and media that will be used to achieve the target the intended audience. After analysis of the data, the found a concept or design, branding keywords i.e.